La incorporación del principio feminista en la enseñanza de la Teoría del Estado en el contexto del Estado Social y democrático del Derecho Español - Macías Jara, María (2019)
The Constitution of Spain as a social and democratic State of Law represents a point of departure and an objective, a clause of initiation and closure that binds the public authorities in order that, in the exercise of their functions, they comply with the Constitution and the principles and rights recognized therein, as well as the rest of the legal system. The configuration of contemporary democracies has been accompanied by various principles of the configuration of States as States of Law and social States, incorporating principles of undoubted importance and maximum effectiveness, such as the principle of legality, the hierarchy of regulations, the separation of powers, justice or pluralism, among others. However, since the construction of the States, while the value of freedom is raised, equality, particularly the material one, is left aside, whose pending challenge lies in the achievement of the effective equality of women and men as shapers of the people sovereign. In the current configuration of the States, it is necessary to incorporate definitively the principle of gender equality or, as I prefer, feminist principle to elaborate a new social pact, of coexistence and of effective construction of freedom in equality that reverts in the quality of democracies and social States of Law, such as Spanish.